Typology of Hadith Madrasah in the Sham - Raja Syahrul Muaripul Adha; U Yusup Maulana; Isra Mardi; Engkos Kosasih (Al-Hasyimi: Jurnal Ilmu Hadis, 2024)
The region of Sham, which includes Syria, Lebanon, Palestine, and Jordan, has an important role in Islamic history, particularly in the development of hadith science. This study aims to explore the role and characteristics of hadith madrassas in Syam by using the library research method. The results of the study show that Sham is the center of blessings as mentioned in the verses of the Qur'an and the hadith of the Prophet. The companions, such as Mu'adz bin Jabal, Abu Darda, and Ubadah bin Shamit, played an important role in building the hadith madrassa in Sham, followed by the contributions of tabi'in and atba' tabi'in scholars. The hadith madrassa in Sham has its uniqueness, such as the beginning of hadith bookkeeping, the development of hadith criticism, and the lack of hadith forgery in the early days. However, the tradition of narrating hadith without sanad is also a challenge that is then improved through the innovation of scholars such as al-Auza'i and al-Zuhri. Thus, the hadith madrasah in Syam is not only a center of learning but also contributes significantly to maintaining the authenticity of the hadith, making it one of the important pillars in the history of Islamic science.